2017
DOI: 10.1016/j.cct.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A Coaching by Telephone Intervention for Veterans and Care Team Engagement (ACTIVATE): A study protocol for a Hybrid Type I effectiveness-implementation randomized controlled trial

Abstract: This study is the first to test a web-based health risk assessment coupled with a health coaching intervention within a large healthcare system. Results from this study will help the Veterans Health Administration (VHA) implement its national plan to include comprehensive health risk assessments as a tool to engage Veterans in prevention. The results will also inform health systems outside VHA who seek to implement Medicare's advisement that health risk assessment become a mandatory component of care under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…These eight trials started recruitment between 2011 and 2014. Of these trials, one included dyads of patients and caregivers (Van Houtven et al, 2014), four targeted cardiovascular disease risk factors including obesity and hypertension (Jackson et al, 2016;Oddone et al, 2017;Voils et al, 2014;Voils et al, 2016;Zullig et al, 2014;Zullig et al, 2015), one addressed smoking cessation (Wilson et al, 2016), one addressed emergency department follow-up (Hastings et al, 2014), and one addressed osteoarthritis of the knee and hip (Allen et al, 2012; Table 1). The mean participant age was 57.7 years for women and 65.9 years for men.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These eight trials started recruitment between 2011 and 2014. Of these trials, one included dyads of patients and caregivers (Van Houtven et al, 2014), four targeted cardiovascular disease risk factors including obesity and hypertension (Jackson et al, 2016;Oddone et al, 2017;Voils et al, 2014;Voils et al, 2016;Zullig et al, 2014;Zullig et al, 2015), one addressed smoking cessation (Wilson et al, 2016), one addressed emergency department follow-up (Hastings et al, 2014), and one addressed osteoarthritis of the knee and hip (Allen et al, 2012; Table 1). The mean participant age was 57.7 years for women and 65.9 years for men.…”
Section: Resultsmentioning
confidence: 99%
“…In doing so, we found that the proportion of women ranged from 5.1% to 13.3% at the initial data pull, 4.4%-11.7% for mailed recruitment letters, 4.4%-19.2% during attempted to contact for screening, 3.3%-22.0% of those consented, and 3.3%-22.2% of those participants who completed the final outcome assessment. Five studies consented more than 10% women (Hastings et al, 2014;Oddone et al, 2017;Voils et al, 2014;Wilson et al, 2016;Zullig et al, 2014), and all but one of those targeted conditions that are not inherently tied to the patient's age (e.g., smoking, obesity, inactivity, or emergency department use). The one study that did target age-related conditions, specifically hypertension and hyperlipidemia, also aimed to increase recruitment of women (Zullig et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ACTIVATE trial was a randomized controlled trial evaluating enrollment in prevention programs and changes in behavioral activation in Veterans receiving a comprehensive health risk assessment and telephone coaching intervention compared to Veterans receiving health risk assessment and usual care. 32 The study was conducted in three Veterans Health Administration (VHA) primary care clinics in Ann Arbor, Michigan, Durham, North Carolina, and Greenville, North Carolina; the Ann Arbor and Durham VA Medical Centers are academically-affiliated, and the Greenville VA is affiliated with the Durham VA. Eligible Veterans included those who were enrolled in primary care and had at least one modifiable risk factor: BMI ≥ 30, current smoker, and/or less than 150 min of moderate/vigorous physical activity per week.…”
Section: The Activate Trialmentioning
confidence: 99%